Dental noise exposed mice display depressive-like phenotypes. Issue 1 (December 2016) - Dong, Yujie; Zhou, Ying; Chu, Xixia; Chen, Shiqing; Chen, Lei; Yang, Beimeng; Zhang, Xu; Wang, Lin; Wang, Shuai; Lou, Jingyu; Deng, Qing; Wang, Li; et al.
Abstract Background Studies have indicated that depressive disorders are observed frequently in dentists. It's suggested that dentists encounter numerous sources of stress in their professional career. We noticed that the noises in dental environments are very unpleasant. The animal modeling studies suggested that stressful noise could produce depressive-like phenotypes in rodent animals. We hypothesize that the dental noise may be one of the primary stressors causing depressive disorders in dentists. Results We treated C57BL/6 mice with programmatically played wide-spectrum dental noise for 8 h/day at 75 ± 10 dB SPL level for 30 days, and then tested the behaviors. After exposure to dental noise, animals displayed the depressive-like phenotypes, accompanied by inhibition of neurogenesis in hippocampus. These deficits were ameliorated by orally administered with antidepressant fluoxetine. Conclusions Our results suggested that dental noise could be one of the primary stressors for the pathogenesis of depressive disorders and the dental noise mouse model could be used in further depression studies.